Analysis of Pregnancy-Associated Plasma Protein A Production in Human Adult Cardiac Progenitor Cells - D'Elia, Piera (Hindawi Publishing Corporation, 2013)
IGF-binding proteins (IGFBPs) and their proteases regulate IGFs bioavailability in multiple tissues. Pregnancy-associated plasma protein A (PAPP-A) is a protease acting by cleaving IGFBP2, 4, and 5, regulating local bioavailability of IGFs. We have previously shown that IGFs and IGFBPs are produced by human adult cardiac progenitor cells (haCPCs) and that IGF-1 exerts paracrine therapeutic effects in cardiac cell therapy with CPCs. Using immunofluorescence and enzyme immunoassays, we firstly report that PAPP-A is produced and secreted in surprisingly high amounts by haCPCs. In particular, the homodimeric, enzymatically active, PAPP-A is secreted in relevant concentrations in haCPC-conditioned media, while the enzymatically inactive PAPPA/proMBP complex is not detectable in the same media. Furthermore, we show that both homodimeric PAPP-A and proMBP can be detected as cell associated, suggesting that the previously described complex formation at the cell surface does not occur easily, thus positively affecting IGF signalling. Therefore, our results strongly support the importance of PAPP-A for the IGFs/IGFBPs/PAPP-A axis in CPCs biology.